Imputed gene associations identify replicable trans‐acting genes enriched in transcription pathways and complex traits. Issue 6 (4th April 2019) - Wheeler, Heather E.; Ploch, Sally; Barbeira, Alvaro N.; Bonazzola, Rodrigo; Andaleon, Angela; Fotuhi Siahpirani, Alireza; Saha, Ashis; Battle, Alexis; Roy, Sushmita; Im, Hae Kyung
Abstract: Regulation of gene expression is an important mechanism through which genetic variation can affect complex traits. A substantial portion of gene expression variation can be explained by both local ( cis ) and distal ( trans ) genetic variation. Much progress has been made in uncovering cis ‐acting expression quantitative trait loci ( cis ‐eQTL), but trans ‐eQTL have been more difficult to identify and replicate. Here we take advantage of our ability to predict the cis component of gene expression coupled with gene mapping methods such as PrediXcan to identify high confidence candidate trans ‐acting genes and their targets. That is, we correlate the cis component of gene expression with observed expression of genes in different chromosomes. Leveraging the shared cis ‐acting regulation across tissues, we combine the evidence of association across all available Genotype‐Tissue Expression Project tissues and find 2, 356 trans ‐acting/target gene pairs with high mappability scores. Reassuringly, trans ‐acting genes are enriched in transcription and nucleic acid binding pathways and target genes are enriched in known transcription factor binding sites. Interestingly, trans ‐acting genes are more significantly associated with selected complex traits and diseases than target or background genes, consistent with percolating trans effects. Our scripts and summary statistics are publicly available for future studies of trans ‐acting gene regulation.